Assessing subjective cannabis effects in daily life with contemporary young adult language. (1st January 2022) - Cloutier, Renee M.; Calhoun, Brian H.; Lanza, Stephanie T.; Linden-Carmichael, Ashley N.
Abstract: Introduction: Subjective ratings of cannabis effects are important predictors of use-related consequences. However, psychometric research is fairly limited, particularly for measures to capture variability in daily life when diverse modes of cannabis administration and co-substance use are common. Methods: This study evaluated the predictive utility of a revised item to assess perceived cannabis effects and examined modes of cannabis administration and alcohol and nicotine co-use as moderators. Participants were 106 young adults (18–25 years; 51% female) who completed up to 14 consecutive daily reports of substance use ( n = 1405 person-days). Two measures of subjective effects were examined: a standard item (0–100 rating of "how high do you feel?") and a revised item that uses four crowd-sourced anchor points ranging from relaxed (0), calm/chill (33), high (67), and stoned/baked (100). The items shared substantial variance (Pseudo- R 2 = 59.5%), however, the revised item showed greater within-person variability (77.0% vs. 68.8%) and stronger day-level associations with consumption levels (Pseudo- R 2 = 25.0% vs. 16.7%). Results: The cannabis consumption-subjective effects link was weaker on blunt-only days compared to vape-only days. Subjective cannabis effects were higher on nicotine co-use days after controlling for cannabis consumption; neither alcohol nor nicotine co-use moderated the cannabis consumption-subjective effects link. Discussion: The revised subjective cannabis effects item is a viable alternative to the standard item among young adults who engage in simultaneous alcohol and cannabis use. Conclusions: Future research focused on characterizing the variability in cannabis effects is needed. Highlights: Subjective cannabis effects may be measured with a revised item incorporating contemporary young adult language Subjective cannabis effects & number of hits were positively linked; effects weakened when smoking blunts or joints vs vaping. Subjective cannabis effects were higher on days cannabis was co-used with nicotine, but not alcohol. As cannabis use is decriminalized in the US, cannabis measures should incorporate contemporary young adult language